2016
DOI: 10.1016/j.gene.2016.01.036
|View full text |Cite
|
Sign up to set email alerts
|

RNA-sequencing study of peripheral blood monocytes in chronic periodontitis

Abstract: Background Monocytes are an important cell type in chronic periodontitis (CP) by interacting with oral bacteria and mediating host immune response. The aim of this study was to reveal new functional genes and pathways for CP at monocyte transcriptomic level. Methods We performed an RNA-sequencing (RNA-seq) study of peripheral blood monocytes (PBMs) in 5 non-smoking moderate to severe CP (case) individuals vs. 5 controls. We took advantage of a microarray study of periodontitis to support our findings. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…As S100A12 gene expression is very sensitive to low levels of LPS (12), we speculate that higher exposure to LPS in periodontitis might be at least partially responsible for the enhanced S100A12 expression seen in this study. In fact, transcriptome analysis of circulating monocytes in periodontitis evidenced they might be more functionally active, with the identification of several genes that interact with invading microorganisms or respond to LPS stimulation (35).…”
Section: Discussionmentioning
confidence: 99%
“…As S100A12 gene expression is very sensitive to low levels of LPS (12), we speculate that higher exposure to LPS in periodontitis might be at least partially responsible for the enhanced S100A12 expression seen in this study. In fact, transcriptome analysis of circulating monocytes in periodontitis evidenced they might be more functionally active, with the identification of several genes that interact with invading microorganisms or respond to LPS stimulation (35).…”
Section: Discussionmentioning
confidence: 99%
“…Lundmark et al . reported the expression of apoptosis‐related genes in gingival tissues, and Liu et al . demonstrated that apoptotic proteins were upregulated in peripheral blood monocytes of patients with chronic periodontitis by DNA microarray studies.…”
Section: Discussionmentioning
confidence: 99%
“…39 Kasprzak et al 40 demonstrated the greater expression of apoptotic protein Bcl-2 in gingival tissues of patients with chronic periodontitis. Lundmark et al 41 reported the expression of apoptosisrelated genes in gingival tissues, and Liu et al 42 demonstrated that apoptotic proteins were upregulated in peripheral blood monocytes of patients with chronic periodontitis by DNA microarray studies.…”
Section: Discussionmentioning
confidence: 99%
“…To begin with, the sample size used in this work was somewhat little although comparable to other publications using next-generation sequencing (RNA-seq) in other diseases and circulating monocytes. 15,60,61 Consequently, we were only able to identify one miRNA showing clear changes between groups. Therefore, other miRNAs with slighter changes in their expression might have not been identified.…”
Section: Hsa-mir-939-3pmentioning
confidence: 99%